Social prescription and trust in older adults: A view in COVID-19 context - Romero-Albino, Zoila (2021)
Background: This article aims to carry out a review on social prescription and trust regarding the deployment of social benefits in the Elderly Centers (CAM) of the Social Health Security (EsSalud) during the health emergency due to COVID-19. EsSalud in its 126 CAM provides social benefits to older adults, that is, activities for the use of free time that are linked to social prescription; that when the sanitary emergency was decreed they turned to the virtual modality. Experience in the face of the pandemic indicates that trust in institutions varies around the decisions made; helping to maintain it, measures such as transparency, collaboration between stakeholders, among others; Aspects of interest if you want the population to follow the health guidelines provided. In this sense, we propose that social prescription activities can contribute to the improvement of trust, and must carry out binding research for decision-making.